The US Opioid Epidemic and Its Impact on US General Practice Veterinarians - Kogan, Lori; Hellyer, Peter; Rishniw, Mark; Schoenfeld-Tacher, Regina (Frontiers in Veterinary Science, 2019)
Objective: To assess the impact of the human opioid epidemic and associated shortages in drug supply on US veterinarians. Design: Cross-sectional study Sample: Members of the Veterinary Information Network (VIN) Procedures: An electronic survey was used to examine veterinarians’ views regarding opioid use in veterinary medicine and the impact of the opioid shortage on the provision of care. The survey was distributed via the VIN data collection portal from October 12, 2018- November 6, 2018. Results: 697 veterinarians completed the survey. Most (99.7%) reported using, dispensing or prescribing opioids in veterinary practice. The most commonly used opioids were buprenorphine, tramadol and butorphanol. While most veterinarians (83.3%) reported difficulty in ordering opioids over the last 6 months, this decreased to 59.0% in the last month. The most difficult drugs to obtain were hydromorphone, morphine, injectable fentanyl and oxymorphone. The reported rate of difficulty in obtaining all these drugs lessened over time. However, the opioid shortage caused significant difficulty in providing appropriate pain management for 41.1% of participants, and affected the ability of 44.8% of respondents to provide optimal anesthesia. Conclusions and Clinical Relevance: Veterinarians’ ability to care for their patients been impacted by the opioid shortage, with a greater impact on full mu opioid agonists as compared to drugs like butorphanol, buprenorphine, and tramadol. The results confirm the important role of opioid analgesics in the delivery of modern veterinary medicine and highlight the importance of medical health professionals being able to access these critical medications.